Cytogenetical analysis of 12 taxa of Genista L. (Fabaceae) from Turkey - Martin, Esra; Dinc, Muhittin; Duran, Ahmet; Dogan, Bekir; Hakki, Erdogan E. (Bangladesh Journal of Plant Taxonomy, 2009)
In this study, cytogenetical analyses of 12 taxa belonging to the genus Genista L. and grown naturally in Turkey were conducted. These taxa include G. acanthoclada, G. albida, G. anatolica, G. aucheri, G. burdurensis, G. carinalis, G. involucrata, G. januensis subsp. lydia, G. sandrasica, G. sessilifolia, G. tinctoria and G. vuralii. Chromosome numbers of all the taxa, except G. tinctoria, are introduced to the scientific community for the first time. Somatic metaphase chromosomes of the genus were determined as 2n = 18, 36, 46, 48, 52, 72 and 144. Polyploidy was observed in the cells of G. albida (2n = 18, 2n = 4x = 36), G. tinctoria (2n = 36, 48, 2n = 4x = 96), G. januensis subsp. lydia (2n = 46, 2n = 4x = 92), G. burdurensis and G. sessilifolia (2n = 48, 2n = 4x = 96). Somatic chromosomes of the G. sandrasica are very small, thus exact ploidy level of polyploidy was not determined. Karyotype analysis of G. albida and G. involucrata were performed via an Image Analysis System. Keywords: Genista; Leguminosae; chromosome number; karyotype; Turkey. DOI: 10.3329/bjpt.v16i2.3927 Bangladesh J. Plant Taxon. 16(2): 151-156, 2009 (December)